Upaya Guru PAI dalam Meningkatkan Kecerdasan Emosi dan Komunikasi Siswa di SMAN 11 Merangin: Penelitian - Meifa Adinda Erwina; Martin Kustati; Nana Septriyanti (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to describe the efforts of Islamic Religious Education (PAI) teachers in enhancing the emotional intelligence and communication skills of tenth-grade students at SMA Negeri 11 Merangin. The background of this research is based on the importance of developing emotional and social aspects as part of a holistic education approach, considering that many students still face difficulties in managing emotions and interacting effectively. This study employs a qualitative approach with a case study method to explore the strategies implemented by PAI teachers and to identify the supporting and inhibiting factors encountered during the learning process. The findings reveal that PAI teachers apply three main approaches: preventive, developmental, and curative. The preventive approach involves instilling values such as self-control, empathy, and tolerance through contextual learning and communication with parents. The developmental approach is carried out through interactive learning methods such as group discussions and role-playing activities, while the curative approach includes individualized mentoring and collaboration with guidance and counseling teachers for students experiencing emotional and communication challenges. The consistent integration of Islamic values within the learning process has proven effective in strengthening students' character, enhancing emotional intelligence, and fostering healthy communication. The success of these strategies is supported by the strong commitment of PAI teachers and a conducive school environment, although challenges such as limited instructional time, lack of family support, and internal student factors remain.